KATA MAJEMUK DALAM BAHASA INDONESIA (SEBUAH TELAAH KOMPREHENSIF) - Warsiman (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2016)
This writing aims giving deeper understanding to Indonesia users about clauses, phrases, and idioms so that they are able to differ those terms. The scope of this writing is about verb clause, noun clause, adjektive clause and the parts, phrases, and idioms. The method used in this writing is qualitative descriptive method. The result and the conclution is to be the good Indonesian users, understand about the clause (verb clause, naoun clause, and adjective clause), phrases, and idioms absolutely needed them the users are not trapped in misunderstanding the different of those clauses, phrases and idioms as clauses. The same form showed by those group of words is almost can not distinguised expert by understanding the special characteristic owned and showed by those group of word.